Dynamic evolution of coal nanopores during CO2 adsorption after progressive immersion-drying damage: An in situ SAXS study - Chengxi Wang; Yixin Zhao; Shuaipeng Zhu; Xiaodong Guo; Yingfeng Sun (Gas Science and Engineering, 2026)

Functional interaction between Bacillus velezensis D103 and maize reveals a microbial mechanism for drought stress mitigation via photosynthesis and sugar metabolism - Yating Zhang; Zhenqiang Feng; Yanling Guo; Yingfeng An; Zhiyong Zhang; Xinyue Bi; Bo Zhang; FangFang Yu; Tong Bi; Faryal Babar Baloch; Jianjia Miao; Yunjiao Wang; et al. (Plant Science, 2026)

Summer Thermal Comfort Zoning Studies of Mainland China Based on the Comprehensive Heat Index - Yingfeng Guo; Zhifeng Wu; Zihao Zheng; Xiaojun Huang; Zhongwen Hu (International Journal of Climatology, 2025)
With global warming, a better understanding of the summer thermal environment is crucial. Distinct from land surface temperature, which is the most widely noticed and employed parameter of the summer thermal environment, we constructed the Summer Comprehensive Heat Index using six common heat indices (outdoor apparent temperature, heat index, Humidex, modified discomfort index, net effective temperature, and simplified wet‐bulb global temperature) through principal component analysis, analysing its spatial distribution and temporal trends (2003–2020) at 10 km grid and county scales across mainland China. Employing Automatic Regionalisation with Initial Seed Location, Regionalisation with Dynamically Constrained Agglomerative Clustering and Partitioning, and Spatial Kluster Analysis by Tree Edge Removal regionalisation methods with spatially constrained and classical statistical approaches, a two‐tier geographical division of summer thermal comfort zones was conducted. Results indicate severe thermal stress in Southern China and the Bohai Rim regions, while regions such as the marginal region of the Tibetan Plateau, Inner Mongolia Plateau, and Yungui Plateau offer high thermal comfort, suitable for ‘sunbird’ tourism. Conversely, the Bohai Rim and lower Yangtze regions exhibit extreme heat stress with intensifying warming trends, calling for urgent adaptation. The study highlights regional thermal heterogeneity, providing insights for localised tourism planning and climate resilience strategies.

Logic combination and diagnostic rule-based method for consistency assessment and its application to cross-sensor calibrated nighttime light image products - Zihao Zheng; Qiming Zheng; Zhifeng Wu; Zheng Cao; Hong Zhu; Yingbiao Chen; Benyan Jiang; Yingfeng Guo; Dong Xu; Francesco Marinello (Remote Sensing of Environment, 2025)

Application of opposing coils transient electromagnetic method in urban area with metal interference - Juan Fan; Enke Hou; Dewu Jin; Zhenzhu Xi; Xia Long; Sheng Zhou; Shenghui Nan; Yingfeng Liu; Kang Guo; Dianyan Ning (Journal of Applied Geophysics, 2024)

Fluorescent cellulose nanofibrils-based hydrogel incorporating MIL-125-NH2 for effective adsorption and detection of iodide ion - Xuefeng Zhang; Xinmiao Qi; Jiayu Ouyang; Yingfeng Zuo; Qiang Ma; Haining Tan; Xin Guo; Yiqiang Wu (Journal of Hazardous Materials, 2024)

A Fluorescence Biosensor Based on Carbon Quantum Dots Prepared from Pomegranate Peel and T-Hg2+-T Mismatch for Hg2+ Detection - Weiqin Zhao; Chun Huang; Xiyu Guo; Youyu Zhu; Yuangang Li; Yingfeng Duan; Jie Gao (Journal of Fluorescence, 2024)

Assessing drought variability since 1650 AD from tree‐rings on the Jade Dragon Snow Mountain, southwest China - Yingfeng Bi; Jianchu Xu; Aster Gebrekirstos; Liang Guo; Mingxu Zhao; Eryuan Liang; Xuefei Yang (International Journal of Climatology, 2015)
Southwest China has experienced significant drought during the past few years. To better understand the tendency of drought changes over time, this study applies dendroclimatological techniques to assess drought variations in Lijiang Prefecture, southwest China. So far, the longest chronology (387 years) of Picea likiangensis on the Jade Dragon Snow Mountain was constructed, and the relationships between the tree‐ring width and climate variables were analysed. The spring season Palmer Drought Severity Index ( PDSI ) was reconstructed based on a standard chronology. Tree‐ring width is positively related to precipitation and relative humidity from February to March and the PDSI from January to May. Conversely, tree‐ring width is also negatively related with mean temperature from January to May, suggesting that growth of P. likiangensis is affected both by temperature and precipitation. The reconstructed PDSI showed that the Jade Dragon Snow Mountain has experienced considerable variations in spring drought conditions during the past 361 years. Four distinct periods were recognized: (1) 1650–1730, a relatively humid period with an average PDSI value above zero; (2) 1730–1860, a period with greatly fluctuating PDSI and intermittent wet periods (1746–1755, 1782–1800, and 1820–1830) and several dry periods (1735–1745, 1756–1780, 1810–1820, and 1830–1860); (3) 1870–1945, a humid period, with the highest PDSI value during 1930–1945; and (4) 1945–2011, a period with decreasing humidity. The results are consistent with hydrological studies in nearby regions and related species, as well as historical records of natural disasters. The recently observed spring drought follows a trend of decreasing humidity over the past 60 years, suggesting that a sound strategy for management and land‐use planning is required to secure ecosystem and human well‐being.